Corporate responsibility and labour rights : codes of conduct in the global economy - Jenkins, Rhys Owen, 1948-; Pearson, Ruth, 1945-; Seyfang, Gill, 1969- (Earthscan, 2002)
The emergence of voluntary corporate codes of conduct since the early 1990s is both a manifestation of and a response to the process of globalization. They have been part of a more general shift away from state regulation of transnational corporations towards corporate self-regulation in the areas of labour and environmental standards and human rights. This work provides a critical perspective on the growth and significance of corporate codes with a particular focus on working conditions and labour rights. It brings together work by academics practitioners and activists.